Relationship Marketing By Energy Companies - Felicetta IOVINO (Revista de Management Comparat International)
New two hour schedule tariffs were introduced on 1st July 2010 by AEEG. They distinguish use of electric energy between night and daylight hours and Sundays and public holidays, creating three different price bands (F1, F2, F3), thus eliminating one hour schedule tariff for the vulnerable customers. This study is proposed to understand the basic research problem “How much Italian energy companies have implemented relationship marketing and what are the characteristics of their marketing policies”. We suggest this approach increases competition which is the aim of liberalization processes. In fact, according to the principle of the “conservation of relationship energy”, an Uppsala model, relationship energy cannot be destroyed and it can only be transformed and transferred to other relationships, manifesting itself in a variety of ways. So if relationship marketing is better implemented switching increases but trade relationships can be reactivated at a later time by social links which continue during the time. To answer that question we compare the data of three recent researches that analyze switching energy supplier in Italy, the UK and State of Victoria in Australia.